Modern narratives and film adaptation as translation - doi: 10.4025/actascilangcult.v35i3.17238 - Silva, Carlos Augusto Viana da (Acta Scientiarum. Language and Culture, 2013)
This paper analyses the translation of the modern narratives Mrs. Dalloway (1976), by Virginia Woolf; A Portrait of the Artist as a Young Man (1994) and The Dead (1993), by James Joyce, into the films Mrs. Dalloway (1997) by Marleen Gorris, A Portrait of the Artist as a Young Man (1977) by Joseph Strick, and The Dead (1987) by John Huston. Based on the principles of the polysystem theory (EVEN-ZOHAR, 1990) and on the idea of film adaptation as translation (CATTRYSSE, 1992), contextual aspects of the process of creation and reception of these adaptations will be discussed, as well as their role in the representation of the writers’ literary universe to spectators.